RESEARCH DESIGN FOR ORAL EXEGESIS IN INDONESIA (A STUDY OF MUHAMMAD SYA’RONI AHMADI’S EXEGESIS) - Ulin Nuha (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2024)
This article aims to construct a methodological framework for researching oral Quranic exegesis in Indonesia and to apply it to the oral interpretations of Muhammad Sya’roni Ahmadi. The study employs a library research method, utilizing literature regarding the methodology of Quranic exegesis in Indonesia and the specific interpretations of Muhammad Sya’roni Ahmadi. The findings indicate that oral exegesis can be analyzed through several methodological aspects: the exegetical method, the exegetical orientation (laun), the systematic structure and form of presentation, the delivery style, the publication platform, and the social identity of the exegete. Furthermore, the substance of oral exegesis can be examined through the characteristics of orality, tanzīlī analysis, and discourse analysis. Muhammad Sya’roni Ahmadi’s interpretation of Surah Al-Mumtahanah [60]: 8–9 exhibits characteristics of orality through the use of the Javanese language and the inclusion of stories involving Raden Rahmat, Raden Patah, and King Brawijaya to foster a sense of closeness with the audience. These stories demonstrate a tanzīl dynamic that is both taṣrīḥ (explicit) and kullī (holistic), while simultaneously conveying a message for Muslims to adopt a friendly attitude toward non-Muslims.